2021
DOI: 10.3390/microorganisms9040792
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Diversity of Selected Habitat Specific Cynorkis Species (Orchidaceae) in the Central Highlands of Madagascar

Abstract: About 90% of Cynorkis species are endemic to the biodiversity hotspot of Madagascar. This terrestrial habitat-specific genus received little study for fungal diversity to support conservation. We evaluated the diversity of culturable fungi of 11 species and soil characteristics from six sites spanning a >40 km radius in and along the region’s inselbergs. Peloton-forming fungi were grown in vitro from root/protocorm slices and positively identified using DNA sequencing. The fungal diversity was then correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…As this site is hosting a diverse range of orchids seed-germination-compatible Tulasnella OTU from southern marsh orchid (from a chalky wet habitat) was tested among many other isolates of putative mycorrhizal fungi for yellow early marsh. The lineage of Tulasnellaceae, a common mycorrhizal fungus in orchids shows generalist behavior as reported in many Dactylorhiza and other terrestrial orchids [ 28 , 29 , 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…As this site is hosting a diverse range of orchids seed-germination-compatible Tulasnella OTU from southern marsh orchid (from a chalky wet habitat) was tested among many other isolates of putative mycorrhizal fungi for yellow early marsh. The lineage of Tulasnellaceae, a common mycorrhizal fungus in orchids shows generalist behavior as reported in many Dactylorhiza and other terrestrial orchids [ 28 , 29 , 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 85%
“…In three terrestrial orchids, it is demonstrated that one Tulasnella strain exhibited high compatibility across the three distantly related host species showing the generalist nature of this lineage of mycorrhizal fungus [ 29 ]. Studies in several species of the terrestrial genus of Cynorkis from Madagascar and found that most of those species recruited fungi of Tulasnella lineage at various growth phases and under different soil conditions [ 31 ]. In the current study the donor orchid, D. praetermissa was from a moist chalky site while the recipient orchid was from a chalky fen habitat.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among lithophytic and epiphytic individuals of Coelogyne corymbosa, Serendipitaceae fungi contributed a relatively large portion of the OTU communities specific to lithophytic orchids (Qin et al, 2020). Yokoya et al (2021) surveyed 11 growing Cynorkis orchid species within lithophytic and terrestrial habitats and found that Serendipitaceae OTUs were frequently found in species inhabiting granite/rock, whereas Tulasnellaceae OTUs were found in both habitat types; they also reported that most Serendipitaceae OTUs were found in the habitat with higher phosphorus and nitrogen content, which may indicate that Serendipitaceae prefers soil conditions with high phosphorus and nitrogen levels. These differences in nutrient conditions may contribute to OMF community differences between lithophytic and epiphytic individuals in D. officinale.…”
Section: Discussionmentioning
confidence: 99%